Catalyst‐ and Solvent‐Free Synthesis of a Chemically Stable Aza‐Bridged Bis(phenanthroline) Macrocycle‐Linked Covalent Organic Framework. (26th June 2021) - Jiang, Yi; Jung, Hyeonjung; Joo, Se Hun; Sun, Qi Kun; Li, Changqing; Noh, Hyuk‐Jun; Oh, Inseon; Kim, Yu Jin; Kwak, Sang Kyu; Yoo, Jung‐Woo; Baek, Jong‐Beom
Abstract: Developing new linkage‐based covalent organic frameworks (COFs) is one of the major topics in reticular chemistry. Electrically conductive COFs have enabled applications in energy storage and electrochemical catalysis, which are not feasible using insulating COFs. Despite significant advances, the construction of chemically stable conductive COFs by the formation of new linkages remains relatively unexplored and challenging. Here we report the solvent‐ and catalyst‐free synthesis of a two‐dimensional aza‐bridged bis(phenanthroline) macrocycle‐linked COF (ABBPM‐COF) from the thermally induced poly‐condensation of a tri‐topic monomer and ammonia gas. The ABBPM‐COF structure was elucidated using multiple techniques, including X‐ray diffraction analysis combined with structural simulation, revealing its crystalline nature with an ABC stacking mode. Further experiments demonstrated its excellent chemical stability in acid/base solutions. Electrical‐conductivity measurements showed that the insulating ABBPM‐COF becomes a semiconducting material after exposure to iodine vapor. Abstract : A 2D aza‐bridged bis(phenanthroline)‐macrocycle‐linked conjugated covalent organic framework (COF) was constructed by periodically linking hexaaza‐triphenylene units together using the linkage of the aza‐bridged bis(phenanthroline) macrocycle in the absence of solvents and catalysts. The bulk insulating COF pellet became semiconducting after exposure to iodine vapor.